2018
DOI: 10.3390/en11082002
|View full text |Cite
|
Sign up to set email alerts
|

Data Envelopment Analysis in Energy and Environmental Economics: An Overview of the State-of-the-Art and Recent Development Trends

Abstract: Measurement of environmental and energy economics presents an analytical foundation for environmental decision making and policy analysis. Applications of data envelopment analysis (DEA) models in the assessment of environmental and energy economics are increasing notably. The main objective of this review paper is to provide the comprehensive overview of the application of DEA models in the fields of environmental and energy economics. In this regard, a total 145 articles published in the high-quality interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 164 publications
(177 reference statements)
0
48
0
Order By: Relevance
“…The results of the Data Envelopment Analysis (DEA) model are used to compare the relative efficiency between decision units. If DEA methods are integrated with a different technique, it can solve problems and measurethe relative efficiency in different application areas [25]. Han proposed that the fuzzy DEA interaction model can be used to improve the energy efficiency of chemical products [26].…”
Section: Dea Model For Measuring Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the Data Envelopment Analysis (DEA) model are used to compare the relative efficiency between decision units. If DEA methods are integrated with a different technique, it can solve problems and measurethe relative efficiency in different application areas [25]. Han proposed that the fuzzy DEA interaction model can be used to improve the energy efficiency of chemical products [26].…”
Section: Dea Model For Measuring Efficiencymentioning
confidence: 99%
“…Pérez-López used the DEA model to analyze the evolution of economies of scale and propose strategies for achieving long-term economies of scale based on management practices [27]. DEA analysis also is a common method of evaluating energy efficiency [25]. Since there is no assumption about the function form or the distribution of the error term of the production function [28], it can better reflect the information and characteristics of the evaluation object itself.…”
Section: Dea Model For Measuring Efficiencymentioning
confidence: 99%
“…In DEA practices, the variable selection of input and output is a very important issue, where the purpose is to measure the efficiency of each DMU [19][20][21][22]. A relatively comprehensive obtained dataset can provide us with a more reasonable way to represent the evaluation problem.…”
Section: Variables and Data For Unified Efficiencymentioning
confidence: 99%
“…Furthermore, one study [11] states that "DEA showed great promise to be a good evaluative tool for future analysis on energy efficiency" as a conclusion. One of the reasons for this great promise is the facility of multiple inputs and multiple outputs of the DEA model.…”
Section: Dea Bcc Model and Non-decreasing Returns To Scalementioning
confidence: 99%